Correlation between microbial diversity and toxicity of sludge treating synthetic wastewater containing 4-chlorophenol in sequencing batch reactors. (June 2016) - Zhao, Jianguo; Chen, Xiurong; Bao, Linlin; Bao, Zheng; He, Yixuan; Zhang, Yuying; Li, Jiahui
Abstract: The relationship between microbial diversity and sludge toxicity in the biotreatment of refractory wastewater was investigated. Synthetic wastewater containing 4-chlorophenol (4-CP) was treated by an activated sludge using a sequencing batch bioreactor (SBR). At the end of a single SBR cycle, a stable operation stage was reached when the 4-CP was not detected both in aqueous and sludge phases and the effluent COD was maintained at approximately 70 mg L −1 for the blank and control sludge groups. Then, the diversity of the microorganisms and the sludge toxicity were measured. The results showed that the Microtox acute toxicity of the control sludge was higher than those of the blank sludge. The difference analysis of the microbial diversity between the blank and control sludge indicated that the sludge toxicity was closely related to microbial diversity. Highlights: The Microtox acute toxicity was significantly increased as 4-chlorophenol was in the influent. The microbial diversity changed greatly after the sludge was acclimated with 4-chlorophenol. The higher toxicity of the control sludge was closely related to the microbial diversity.